Fluoride levels in commercially available rice in Ethiopia - B.S. Chandravanshi; B. Tegegne; F. Zewge (Bulletin of the Chemical Society of Ethiopia, 2013)
Rice (Oryza sativa, Asian; Oryza glaberrima, African) is an important staple food crop in many Sub-Saharan African and Asian countries, so the consumer’s daily bowl of rice needs to be safe and of good quality. The objective of this study was to determine level of fluoride in raw and cooked rice by ion selective electrode. Alkaline fusion was used for sample preparation of six varieties for both the raw rice and rice cooked with tap water and fluoridated water. Fluoride levels ranged from 0.1-5.5 mg/kg in raw rice sample. Rice which was cooked with different fluoride levels of water showed increment depending on the method of cooking. In absorption method of cooking fluoride level was higher than that cooked by excess method and it may be due to the fact that all the fluoride in the water used for cooking by absorption method goes in to the grain while in excess method the remaining water was removed. The employed alkaline fusion procedure was evaluated using spiking method and an acceptable percentage recovery was obtained. A statistical analysis of variance at 95% confidence level for fluoride determination indicated significant difference between the mean of each variety of rice samples.